EXPLORING THE IMPACT OF INTERNATIONAL VOLUNTEER TOURISM ON YOUTH TRAVELERS - Tairova Dilnoza Gayratovna (Web of Journals Publishing, 2024)
International volunteer tourism, often referred to as voluntourism, has gained prominence as a unique form of travel that combines the exploration of new cultures with meaningful community service. This article delves into the intersection of international volunteer tourism and youth travelers, examining the motivations, challenges, and potential impacts of this growing phenomenon. By synthesizing existing research and drawing upon case studies, this article aims to contribute to the understanding of the complex dynamics surrounding the involvement of youth in international volunteer tourism.